2011
DOI: 10.1253/circj.cj-11-0025
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Heart Failure - The Role of the .BETA.-Adrenergic Receptor-Mediated Signaling Pathway and p53-Mediated Signaling Pathway in the Apoptosis of Cardiomyocytes -

Abstract: The heart works as a driving force to deliver oxygen and nutrients to the whole body. Interrupting this function for only several minutes can cause critical and permanent damage to the human body. Thus, heart failure (HF) or attenuated cardiac function is an important factor that affects both patient's the quality of life and longevity. Numerous clinical and basic studies have been performed to clarify the complex pathophysiology of HF and to develop effective therapies. Modulating the β-adrenergic receptor-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 78 publications
4
31
0
Order By: Relevance
“…Major mechanism of c-jun mediated suppression of apoptosis is by attenuating expression of pro-apoptotic protein p53 and its target gene noxa [37]. Interestingly, recent studies point towards p53 as a central molecule in mediating cardiomyocyte apoptosis and heart failure (for review see [65]). Although in our study deletion of Jun in heart was restricted to cardiomyocytes, based on our results we cannot define whether deletion of Jun promotes apoptosis of cardiomyocytes directly or rather cardiomyocytes deficient for this protein secrete factor/-s which promotes apoptosis of the neighboring cells in heart.…”
Section: Discussionmentioning
confidence: 99%
“…Major mechanism of c-jun mediated suppression of apoptosis is by attenuating expression of pro-apoptotic protein p53 and its target gene noxa [37]. Interestingly, recent studies point towards p53 as a central molecule in mediating cardiomyocyte apoptosis and heart failure (for review see [65]). Although in our study deletion of Jun in heart was restricted to cardiomyocytes, based on our results we cannot define whether deletion of Jun promotes apoptosis of cardiomyocytes directly or rather cardiomyocytes deficient for this protein secrete factor/-s which promotes apoptosis of the neighboring cells in heart.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the apoptosis, it is surprising that a p53/Caspase-3 independent pathway is being employed. However, there are many ways to trigger apoptosis as both cell culture and zebrafish studies have uncovered p53-independent apoptotic pathways (Fujita and Ishikawa, 2011; Pyati et al, 2007; Sidi et al, 2008). Moreover, a recent study in zebrafish elucidated a conserved Chk1/Caspase-2 dependent and p53/Caspase-3 independent apoptotic pathway (Sidi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that, in patients with end-stage heart failure, the incidence of myocardial apoptosis was 0.08–0.25%, while the normal myocardium apoptosis rate was 0.001-0.002% [8]. Moderate and sustained levels of myocardial apoptosis may lead to heart failure [9]. Therefore, drugs that inhibit cardiomyocyte apoptosis in patients with residual cardiac function may be protective and may delay and inhibit the progression of heart failure.…”
Section: Introductionmentioning
confidence: 99%